(untitled) (Journal of Information Technology and Digital World, 2022)
Fog computing that emerges as an important paradigm, describes decentralized computing architecture between cloud and devices. It includes potential challenges, such as increase in traffic overhead, since all requests are sent to the main server that causes delay, which cannot be tolerated in delay sensitive applications and the usage of inappropriate scheduling causes high power consumption in fog device. These challenges must be overcome by employing effective workload. In this paper, in order to find effective workload allocation based on power and delay tradeoff various scheduling algorithms like SJF (Shortest Job First), FCFS (First Come First Served) and RR (Round Robin) are implemented in fog device and its power and delay trade off are analyzed in fog computing subsystem.